Application of the Project Based Learning (PjBL) Learning Model to Illustration Drawing Skills in Class V of SD Negeri 36 Banda Aceh - nisa, khairun; Fitri, Aida; Husin, M. (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the application of the Project Based Learning (PjBL) learning model to the skills of drawing illustrations for class V at SD Negeri 36 Banda Aceh. The approach used is qualitative with a descriptive type. The subjects were taken by 28 fifth grade students at SD Negeri 36 Banda Aceh. Data collection techniques are observation and performance appraisal. Data were analyzed by data reduction, data presentation and drawing conclusions. Based on the results of research at SD Negeri 36 Banda Aceh the application of the Project Based Learning learning model can improve students' skills towards learning success, because student skills are an important basic element to achieve the success of a project. In this study the students were active in learning activities which could be seen from the actions of the students with the interaction between fellow students in participating in ongoing learning. The application of learning models can be very effective in the learning process because it is more interesting which requires all students to be active in groups, interact with classmates and dare to appear in front of the class, this can reduce student boredom during the learning process. So that the application of the Project Based Learning (PjBL) learning model can be used in illustration drawing skills.